Pengembangan Alat Evaluasi Berbasis Google Apps Script (GAS) untuk Ujian Akhir Semester (UAS) Mahasiswa FTIK UIN Palangka Raya - Mukhlis Rohmadi; Nurul Septiana (Jurnal Ilmiah Matrik, 2026)
Academic integrity in online exams is now facing major challenges due to the penetration of generative artificial intelligence (AI), while conventional platforms such as Google Forms and standard Learning Management Systems (LMS) often fail to provide adequate cheating detection features. This research aims to develop a Computer-Based Test (CBT) evaluation tool based on Google Apps Script (GAS) at FTIK UIN Palangka Raya which integrates anti-cheating features and an automated essay assessment system through AI (strict prompting) instructions. Using the Research and Development (R&D) method with a 4D (Define, Design, Develop, Disseminate) model, this study involved 267 students as trial subjects. The resulting product includes dynamic question management, automatic randomization, and comprehensive student activity logging to monitor behavior during exams. The results of the study showed high effectiveness with a student satisfaction score of 4.9 out of 5. However, challenges were found in the user experience aspect, particularly the triggering of positive-false fraud due to device system notifications and dependencies on network stability. These innovations deliver strategic value through modularity and cost efficiency, effectively filling functional gaps on previous platforms that did not yet support AI-based assessments. As an adaptive solution, this tool strengthens institutional credibility in managing the evaluation of learning outcomes independently in the digital era.